2023
DOI: 10.7189/jogh.13.05003
|View full text |Cite
|
Sign up to set email alerts
|

What are the risk factors for death among children with pneumonia in low- and middle-income countries? A systematic review

Abstract: This review aimed to identify clinical, demographic, and investigation findings that are associated with treatment failure or mortality in children (aged two months to nine years) with pneumonia in LMICs. METHODSWe conducted a systematic search of medical databases MEDLINE, EMBASE, and PubMed (for recent studies not yet indexed on MEDLINE) for studies reporting on factors associated with child pneumonia mortality (August 30, 2020). We mapped search terms to medical subject headings where possible, using Boolea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 140 publications
0
1
0
Order By: Relevance
“…However, moderate hypoxaemia in the range of SpO 2 90–93% carried an increased odds of death, which is similar to findings from other studies that have reported general danger signs, severe malnutrition, or cyanosis conditions, which should almost always result in referral to a high-level facility. 6 Although severe hypoxaemia (SpO 2 <90%) should be a clear indication for referral and admission to a high-level facility, we suggest that moderate hypoxaemia (SpO 2 90–93%) and so-called failed readings should also be considered as clear cause for health-care worker concern and action. What this looks like will depend on the local context and capabilities of the health facility, with some primary care facilities able to offer day-care or short admissions with experienced oversight, giving health-care workers time to observe the child to see whether they are clinically stable, whereas other facilities without this capacity rely more on referral pathways to higher-level facilities.…”
Section: Can a Particular Spo 2 Cutoff Guide Risk-...mentioning
confidence: 74%
See 2 more Smart Citations
“…However, moderate hypoxaemia in the range of SpO 2 90–93% carried an increased odds of death, which is similar to findings from other studies that have reported general danger signs, severe malnutrition, or cyanosis conditions, which should almost always result in referral to a high-level facility. 6 Although severe hypoxaemia (SpO 2 <90%) should be a clear indication for referral and admission to a high-level facility, we suggest that moderate hypoxaemia (SpO 2 90–93%) and so-called failed readings should also be considered as clear cause for health-care worker concern and action. What this looks like will depend on the local context and capabilities of the health facility, with some primary care facilities able to offer day-care or short admissions with experienced oversight, giving health-care workers time to observe the child to see whether they are clinically stable, whereas other facilities without this capacity rely more on referral pathways to higher-level facilities.…”
Section: Can a Particular Spo 2 Cutoff Guide Risk-...mentioning
confidence: 74%
“… 9 , 10 Data from children in hospital with pneumonia show that hypoxaemia on admission to hospital is the strongest predictor of death, with the risk of death varying between studies and settings, but proportional to the severity of hypoxaemia, and elevated even at moderate hypoxaemia of 90–93%. 6 Although the prevalence of hypoxaemia is decreased in non-pneumonia conditions, such as malaria and meningitis, the presence and severity of hypoxaemia is similarly associated with death, as hypoxaemic respiratory failure is a complication of many critical systemic illnesses. 11 , 12 , 13 , 14 , 15 …”
Section: How Should Different Levels Of Hypoxaemia Be Interpreted?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown why this occurred, but it may be related to the 32% decline in new HIV infections between 2014 and 2015, which represented the largest decline in many years 26 . HIV is a key risk factor for pneumonia deaths among children <5 years linked and is associated with a 4-fold increased risk of pneumonia death 27 . Additional declines in pneumonia case-fatality rates even after 2015 might also reflect improvements in the quality of healthcare during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…This study conducted a comprehensive analysis of preschool children's pneumonia cases in Urumqi, focusing on the association with indoor environmental factors. Pediatric pneumonia remains a significant public health challenge, especially in low- and middle-income countries, where it continues to be one of the leading causes of child mortality [ [9] , [10] , [11] ]. Our findings align with global research, highlighting the substantial impact of indoor environmental factors, such as passive smoking, housing types, flooring materials, and dampness, on the incidence of pneumonia in children [ 5 ].…”
Section: Discussionmentioning
confidence: 99%